Reducing high risk of cardiovascular events in Type 2 diabetes mellitus: DIALOG Study results - I. E. Sapozhnikova; E. I. Tarlovskaya; A. A. Sobolev; E. V. Rodygina (Кардиоваскулярная терапия и профилактика)
Aim. To study the real-world pharmaceutical reduction of high cardiovascular disease (CVD) risk in patients with Type 2 diabetes mellitus (DM-2).Material and methods. In total, 200 DM-2 patients agreed to participate in the study, including survey, anthropometry, and laboratory tests.Results. In two-thirds of the patients, carbohydrate metabolism was decompensated due to inadequate disease awareness, inadequate or absent glycemia self-control, and rare prescription of combined therapy. The main reasons for not achieving target blood pressure (BP) levels included high rates of monotherapy, low doses of antihypertensive drugs, inadequate treatment compliance, and low rates of BP self-control. Statins were taken by 23% of the patients, and aspirin medications – by 16%.Conclusion. In real-world clinical settings, a substantial proportion of DM-2 patients require intensified treatment, in accordance with the concept of multi-factorial risk reduction.